2020
DOI: 10.1186/s12885-020-07051-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of liver fibrosis score on prognosis after common therapies for intrahepatic cholangiocarcinoma: a propensity score matching analysis

Abstract: Background: Liver fibrosis or cirrhosis is associated with the dismal prognosis of hepatocellular carcinoma (HCC), and it might also be involved in intrahepatic cholangiocarcinoma (ICC). The effect of hepatic fibrosis on the survival of ICC patients is still unclear. This study aims to explore whether liver fibrosis impacts the overall survival (OS) and disease-specific survival (DSS) of ICC patients. Methods: Data of 729 eligible ICC patients receiving different therapies from the Surveillance, Epidemiology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In the case of cirrhosis, rates were significantly diminished for OS but not for PFS. A plethora of studies analyzed the impact of liver fibrosis or cirrhosis on the survival of patients after surgical resection of an iCCA [ 15 , 16 , 17 , 23 ]. For example, a study by Li et al could identify cirrhosis as an unfavorable prognostic factor in surgically treated iCCA [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of cirrhosis, rates were significantly diminished for OS but not for PFS. A plethora of studies analyzed the impact of liver fibrosis or cirrhosis on the survival of patients after surgical resection of an iCCA [ 15 , 16 , 17 , 23 ]. For example, a study by Li et al could identify cirrhosis as an unfavorable prognostic factor in surgically treated iCCA [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two SEER (Surveillance, Epidemiology, and End Results)-based analyses investigated the impact of fibrosis in large cohorts on survival after surgery and non-surgical therapies. Thereby, Zhang et al demonstrated that high fibrosis scores were associated with poor clinical outcomes [ 15 ]. Correspondingly, Levy et al showed that advanced liver fibrosis has an increased risk of both overall and cancer-specific mortality [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inflammation, type II EMT and type III EMT are usually correlated to a certain extent, and type II EMT can induce and enhance type III EMT [ 41 , 42 ]. Therefore, fibrotic diseases are mostly associated with the poor prognosis of tumors [ 43 , 44 ]. In this study, Snail was expressed in the parenchyma but not in the mesenchyme, indicating that a partial EMT occurred in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we were able to establish the association between advanced fibrosis and survival by utilizing the largest cohort to-date, including 512 patients, 192 (37.5%) of whom with advanced fibrosis, and by stratifying the cohort according to both stage and surgical treatment while characterizing how the association differs between groups. Recently, Zhang et al [ 19 ] analyzed an iCCA cohort derived from the SEER database and found that advanced fibrosis was associated with worse overall and cancer specific survival, and worse overall survival in patients following surgery but not for patients that did not undergo surgery. In their study, no stratification according to tumor stage was performed and a multivariable analysis was used only for overall survival assessment on the entire cohort and not for cancer-specific survival or any of the sub-groups.…”
Section: Discussionmentioning
confidence: 99%